Comorbid pathology issues in pediatric gynecology - V.O. Dynnik; N.V. Bagatska; O.O. Dynnik; O.G. Verchoshanova; H.O. Havenko (Group of Companies Med Expert, LLC, 2022)
The problems of diagnosis, therapeutic tactics and medical prognosis in comorbid, polymorbid pathology stand out among the most actual problems of modern health care. Purpose - to study the frequency and nature of comorbid conditions in patients with pubertal abnormal uterine bleeding (PAUB). Materials and methods. The study included 342 girls aged 11-17 suffering from PAUB. All patients were examined by a multidisciplinary team of doctors. Results. It has been shown that menstrual irregularities are combined with other somatic, mental and endocrine pathologies in the vast majority of patients. Only 9.6% of the patients examined had no concomitant pathologies. More than half of girls have a combination of more than three comorbidities. The first three ranks are occupied by endocrine, mental and digestive system disorders. More than a third of patients with endocrine disorders had deviations in terms of body weight - overweight and obesity, which is much more often accompanied by changes in carbohydrate and lipid metabolism. In patients with mental disorders astheno-neurotic syndrome and vegetative-vascular dystonia syndrome prevailed. Functional disorders of the biliary tract were mainly recorded among the disorders of the digestive system, about 18% of girls suffered from gastritis, cholecystitis. The presence of comorbid pathology reduced the effectiveness of non-hormonal therapy by 1.5 times and increased the number of relapses by 3.5-4 times. The effectiveness of non-hormonal therapy was 81.8% on the absence of concomitant pathology; relapses were recorded only in 16.7%. Conclusions. Comorbid pathologies in patients with PAUB aggravate the severity of the girl's condition, reduces adaptive capabilities, adversely affects the effectiveness of non-hormonal therapy, contributes to the recurrence of the disease and is a risk factor for the development of serious metabolic, endocrine and cardiovascular diseases in the future. The category of patients with concomitant pathology requires a special examination algorithm and the appointment of an adequate therapeutic intervention, taking into account all the identified nosological forms and drug compatibility. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of all participating institutions. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.